Improvement of the method of synthesis of δ-Aminolevulinic acid-4-14C hydrochloride - Mitta, Aldo Eduardo Antonio; Ferramola, A. M.; Sancovich,H. A.; Grinstein, M. (1967)
Fil: Mitta, Aldo Eduardo Antonio Comisión Nacional de Energía Atómica; Argentina